Exploring the perceptions of coaches regarding coach-athlete relationships when coaching Generation Z South African academy level rugby union players - Landman, Marc Derek (Stellenbosch : Stellenbosch University, 2024)
Thesis (M Sport Sc)--Stellenbosch University, 2024.